2003
DOI: 10.1021/jp030658+
|View full text |Cite
|
Sign up to set email alerts
|

Radical Yields in the Radiolysis of Branched Hydrocarbons:  Tertiary C−H Bond Rupture in 2,3-Dimethylbutane, 2,4-Dimethylpentane, and 3-Ethylpentane

Abstract: Gel permeation chromatography has been applied to iodine scavenging studies of the distribution of radicals produced in the radiolysis of symmetrically branched hydrocarbons 2,3-dimethylbutane, 2,4-dimethylpentane, and 3-ethylpentane. The principal iodides observed are those expected as a result of simple bond rupture. In the case of 2,3-dimethylbutane all five expected iodides are readily resolvable and it is shown that the loss of H from a tertiary position is favored over loss from a primary position by a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Dihydrocitronellol percent increases from sample A to B, until 1.61%, and then at 1.75% in sample C, being constant in sample D. This supports the fact that radical Ḣ participates in the radiolytic transformations of citronellol, [20,21] because dihydrocitronellol is the product of citronellol's hydrogenation, which could be performed by hydrogen radical. It must be pointed out that the most abundant compounds formed from citronellol by the action of gamma radiation were Nid1 and hydroxycitronellal in the sample D (3%).…”
Section: Irradiated Citronellol Samplessupporting
confidence: 64%
See 2 more Smart Citations
“…Dihydrocitronellol percent increases from sample A to B, until 1.61%, and then at 1.75% in sample C, being constant in sample D. This supports the fact that radical Ḣ participates in the radiolytic transformations of citronellol, [20,21] because dihydrocitronellol is the product of citronellol's hydrogenation, which could be performed by hydrogen radical. It must be pointed out that the most abundant compounds formed from citronellol by the action of gamma radiation were Nid1 and hydroxycitronellal in the sample D (3%).…”
Section: Irradiated Citronellol Samplessupporting
confidence: 64%
“…It is in agreement with previous reports that ionizing radiation acts preferably on the functional groups of the organic compounds. [20,21] In addition, the stability rules of radicals (tertiary > secondary > primary) was considered, as the most stable radicals have more probabilities of participating in the formation of final products of radiolysis. [18][19][20][21] Oxidation mechanism of citronellol Previous theoretical studies about citronellol oxidation to citronellal were not found, neither of similar compounds.…”
Section: Mechanisms Of Citronellol Radiolytic Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial step in this mechanism is the formation of parent alkyl radicals, which in our case can proceed via the abstraction of a H atom by an oxygen-centered radical or by a -irradiation-induced C–H bond rupture. Both processes are expected to be quite selective, producing preferentially tertiary alkyl radicals [32–34]. These radicals, in a series of subsequent reactions involving dioxygen addition, H atom abstraction, and dissociation of the resulting hydroperoxide, give rise to the formation of tertiary alkoxyl radicals (Reaction 1, Scheme 1), which in turn might decompose via -scission (Reaction 2), resulting in the formation of the fragmentary products: methyl ketone and primary alkyl radical.…”
Section: Resultsmentioning
confidence: 99%